Martin Amis’s “State of England” within the Lefebvrean Socio-Spatial Context - Ayyıldız, Nilay Erdem (My University, 2020)
Shedding light on the complicated relationship between space and the human being who goes beyond the physical boundaries of space, Henri Lefebvre made a breakthrough with his critical approach to the urban question through his concept of the “triad of space”, including “perceived space”, referring to the physically perceptible dimension of space; “conceived space”, where the dominant ideologies are operated; and “lived space”, which is peculiar to every inhabitant on the basis of their background. He argued that space is in an incessant process of production, estranging inhabitants in their lived spaces in multicultural and capitalist countries. He posited that “fetishistic concrete abstractions” provide them with romantic domination to cover their alienation and involve them in social relationships in perceived space. England and the protagonist, Big Mal, in Martin Amis’s “State of England” (1998) stand as exemplars for the aforementioned issue. The postmodernist author fictionalizes a lower-class English man’s everyday life in the late twentieth-century England through Mal. It is set in a school garden on a sports day; however, it also portrays Mal’s lived spaces at home, the car park of a bar and even Burger King. In the present study, a Lefebvrean socio-spatial inquiry is employed for scrutinizing England’s urban identity in Amis’s story under question, within the context of capitalism. In this regard, the study indicates that England, undergoing various transformations in the 1990s, is a space of hegemony. In each part of this urban space, Mal oscillates between perceived and conceived spaces and becomes involved in the grindstone of lived space by means of some fetishistic concrete abstractions albeit his alienation. Ultimately, the study concludes that England as a whole is a politicized space which stretches throughout space-time and is always in the process of production by capitalist ideology, influencing everyday lives, especially of lower-class people and the next generation.
Keywords: Henri Lefebvre; socio-spatial theory; multicultural capitalist England; triad of space; fetishistic concrete abstraction.